Correlation between myocardial enzyme serum levels and markers of inflammation with severity of coronary artery disease and Gensini score: A hospital-based, prospective study in Greek patients - Vasileios Peppes (Dove Medical Press, 2008)
Vasileios Peppes, George Rammos, Efstathios Manios, Eleni Koroboki, Stylianos Rokas, Nikolaos ZakopoulosDepartment of Clinical Therapeutics, Alexandra Hospital, University of Athens School of Medicine, Athens, GreeceBackground: Our objective was to associate serum levels of myocardial enzymes and inflammatory biomarkers with severity of coronary artery disease (CAD).Patients and methods: 123 patients participated in our study, including 65 cases of acute myocardial infarction (MI), 27 cases of newly diagnosed CAD – without MI – and 31 controls. In all subjects, myocardial serum enzyme levels (creatine phosphokinase, aspartate aminotransferase, lactate dehydrogenase) and inflammatory indices (C-reactive protein, fibrinogen, white blood cells, and erythrocyte sedimentation rate) were measured. Patients were all submitted to coronary angiography and CAD severity was evaluated by Gensini score.Results: Significant differences concerning enzyme serum levels and inflammatory indices were found to exist between the three study groups, being highest among patients with acute MI (p < 0.001). A significant  association was demonstrated between Gensini score and serum enzyme levels as well as inflammatory biomarkers.Conclusions: Our findings suggest that serum levels of myocardial enzymes and inflammatory indices correlate with CAD severity in Greek patients.Keywords: myocardial enzymes, inflammation, coronary angiography, coronary artery disease